3-MA attenuates collagen-induced arthritis in vivo via anti-inflammatory effect and autophagy inhibition - Chong Feng; Zi-rou Wang; Chen-yu Li; Xiang-yu Zhang; Xin-xing Wang (BMC Musculoskeletal Disorders)
Abstract Background Rheumatoid arthritis (RA) is a chronic autoimmune disease which afflicts about nearly 1% of global population. RA results in synovitis and cartilage/bone damage, even disability which aggravates the health burden. Many drugs are used to relieve RA, such as glucocorticoids (GCs), non-steroidal anti-inflammatory drugs (NSAIDs), and disease-modifying anti-rheumatic drugs (DMARDs) in the clinical treatment. However, present clinical drugs have various disadvantages such as poor bioavailability and short biological half-life and drug resistance, or adverse effects. A recent study showed autophagy modulation may be a novel strategy in the treatment of RA. 3-Methylademine (3-MA), is the most widely used autophagy inhibitor, which blocks autophagy at the initiation and maturation stages. The aim of this study is to evaluate the effect of 3-MA in collagen-induced-arthritis (CIA) mice and further elucidate how 3-MA attenuated inflammation, and cartilage/bone damage in arthritis. Methods An in-vivo mouse collagen-induced arthritis model was applied to compare differences in ankle destruction among control mice and CIA mice treated with or without 3-MA. Bone and cartilage destruction degree was evaluated by histology and micro-computed tomography (µCT). Further in-vivo assays utilized mouse serum samples to investigate inflammatory levels, oxidative levels, and bone resorption cytokines. At last, an immunofluorescence assay was applied to detect the autophagy level among the three groups. Results The in-vivo mouse collagen-induced arthritis model showed that CIA mice revealed apparent hind paw and ankle swelling which was aggravated gradually along with time, while 3-MA treatment attenuated swelling gradually. µCT and histological results showed typical lesions in CIA group while 3-MA treatment alleviated arthritis-related destruction. Serum assay showed that 3-MA significantly reduced inflammatory cytokines levels, suppressed oxidative levels and bone resorption cytokines. Immunofluorescence assay revealed 3-MA significantly inhibited the abnormal autophagy level in CIA mouse ankle. Conclusions 3-MA protects bone destruction in CIA-induced mice arthritis by anti-inflammatory effect and autophagy inhibition.